The role of abnormalities of lipoproteins and HDL functionality in small fibre dysfunction in people with severe obesity - Shazli Azmi (Nature Portfolio, 2021)
Abstract Obesity and associated dyslipidemia may contribute to increased cardiovascular disease. Obesity has also been associated with neuropathy. We have investigated presence of peripheral nerve damage in patients with severe obesity without type 2 diabetes and the status of metabolic syndrome and lipoprotein abnormalities. 47participants with severe obesity and 30 age-matched healthy controls underwent detailed phenotyping of neuropathy and an assessment of lipoproteins and HDL-functionality. Participants with severe obesity had a higher neuropathy symptom profile, lower sural and peroneal nerve amplitudes, abnormal thermal thresholds, heart rate variability with deep breathing and corneal nerve parameters compared to healthy controls. Circulating apolipoprotein A1 (P = 0.009), HDL cholesterol (HDL-C) (P < 0.0001), cholesterol efflux (P = 0.002) and paroxonase-1 (PON-1) activity (P < 0.0001) were lower, and serum amyloid A (SAA) (P < 0.0001) was higher in participants with obesity compared to controls. Obese participants with small nerve fibre damage had higher serum triglycerides (P = 0.02), lower PON-1 activity (P = 0.002) and higher prevalence of metabolic syndrome (58% vs. 23%, P = 0.02) compared to those without. However, HDL-C (P = 0.8), cholesterol efflux (P = 0.08), apoA1 (P = 0.8) and SAA (P = 0.8) did not differ significantly between obese participants with and without small nerve fibre damage. Small nerve fibre damage occurs in people with severe obesity. Patients with obesity have deranged lipoproteins and compromised HDL functionality compared to controls. Obese patients with evidence of small nerve fibre damage, compared to those without, had significantly higher serum triglycerides, lower PON-1 activity and a higher prevalence of metabolic syndrome.